UPAYA PENINGKATAN KUALITAS PELAYANAN PADA UMM MEDICAL CENTER MALANG - Ahmad Faris Royhan (Universitas muhammadiyah malang, 2018)
The purpose of the study was to examine service quality, service attribute, and technical response that should be prioritized based on House of Quality design in Medical Center UMM. This study applied Quality Function Deployment method. The results of the study showed that technical response and service attribute should be developed again. The important aspect of technical response was communication and behavior ethics of staffs. They could make 11 technical responses as strategies to improve service quality in Medical Center UMM.